2013
DOI: 10.1136/annrheumdis-2013-eular.2731
|View full text |Cite
|
Sign up to set email alerts
|

AB0409 An observational study of vitamin d in systemic lupus erythematosus patients: associations among vitamin d status, fatigue, quality of life and disease activity

Abstract: Background Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease in which fatigue and impaired quality of life (QoL) commonly manifest. Fatigue has been associated with increased disease activity in SLE1-3 and both fatigue and disease activity are considered predictors of impaired QoL2-4, although some studies have not reported any association between disease activity and QoL5-6. Objectives The aim of this study was twofold, firstly to determine whether vitamin D is associated with fatigue an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Many studies [23][24][25][26][27] support vitamin D supplementation in pregnant SLE women, emphasizing its anti-inflammatory and immunomodulatory effects. Additionally, a correlation has been observed between vitamin D deficiency and conditions such as PE and miscarriages.…”
Section: Supportive Therapies During Pregnancymentioning
confidence: 99%
“…Many studies [23][24][25][26][27] support vitamin D supplementation in pregnant SLE women, emphasizing its anti-inflammatory and immunomodulatory effects. Additionally, a correlation has been observed between vitamin D deficiency and conditions such as PE and miscarriages.…”
Section: Supportive Therapies During Pregnancymentioning
confidence: 99%
“…Many studies [ 27 , 28 , 29 , 30 , 31 ] support vitamin D supplementation in pregnant women with SLE, emphasizing its anti-inflammatory and immunomodulatory effects. Additionally, a correlation has been observed between vitamin D deficiency and conditions such as PE and miscarriages.…”
Section: Counselingmentioning
confidence: 99%
“…There is a standard agreement that we should offer 25(OH)D to all pregnant women with lupus; however, in clinical practice, we fail to screen these patients, and this is particularly important in those with long-term use of steroids, where data revealed that vitamin D acts as a steroid-sparing agent (48)(49)(50). Another group of patients that should be prioritized in receiving supplements are those with APS.…”
Section: Vitamin D Supplementation In Pregnant Lupus Patientsmentioning
confidence: 99%